The Health Maintenance Function And Health Culture Related To The Implementation Of The Covid-19 Health Protocol In Family At The Village Of Sumuragung Sumberrejo Bojonegoro - Abidin, Ahmad Zainal; Efendi, Yusuf (Journal of Rural Community Nursing Practice, 2023)
Everyone has a strong demand for health, which needs to take on a form essential for adaptability in the Covid-19 pandemic. The culture of health in every human being has altered due to this impact, whether directly or indirectly. To maintain the quality of human health during the Covid-19 pandemic, healthy culture and lifestyle behaviors have become essential to the social structure of health at all levels. This research examines the relationship between health maintenance functions and health culture in relation to the implementation of the covid-19 health protocol in families in the Sumuragung Sumberrejo village, Bojonegoro. This research uses a cross-sectional approach to quantitative research. This study uses Kendall's tau-b statistical test and 10% of the total population of 1719. The study's findings show that 63 respondents (36.6%) fell under the category of family functions: health care, and that 80 respondents (46.5%) fell under the category of health culture: implementation of the Covid-19 health protocol in families. Based on the study's findings, Kendall's tau-b statistical test for these 172 respondents, which used a degree of error of 0.05, produced a p-value of 0.000 and a correlation coefficient of 0.569. In this study, implementing the covid-19 health protocol in families in Sumuragung Sumberrejo village, Bojonegoro, relates to a relationship between health maintenance function and health culture.